IL-1 receptor antagonist, anakinra, prevents myocardial dysfunction in a mouse model of Kawasaki disease vasculitis and myocarditis. (21st June 2019) - Gorelik, M; Lee, Y; Abe, M; Andrews, T; Davis, L; Patterson, J; Chen, S; Crother, T R; Aune, G J; Noval Rivas, M; Arditi, M
Summary: Kawasaki disease (KD) vasculitis is an acute febrile illness of childhood characterized by systemic vasculitis of unknown origin, and is the most common cause of acquired heart disease among children in the United States. While histological evidence of myocarditis can be found in all patients with acute KD, only a minority of patients are clinically symptomatic and a subset demonstrate echocardiographic evidence of impaired myocardial function, as well as increased left ventricular mass, presumed to be due to myocardial edema and inflammation. Up to a third of KD patients fail to respond to first-line therapy with intravenous immunoglobulin (IVIG), and the use of interleukin (IL)-1 receptor antagonist (IL-1Ra, anakinra) is currently being investigated as an alternative therapeutic approach to treat IVIG-resistant patients. In this study, we sought to investigate the effect of IL-1Ra on myocardial dysfunction and its relation to myocarditis development during KD vasculitis. We used the Lactobacillus casei cell-wall extract (LCWE)-induced murine model of KD vasculitis and investigated the effect of IL-1Ra pretreatment on myocardial dysfunction during KD vasculitis by performing histological, magnetic resonance imaging (MRI) and echocardiographic evaluations. IL-1Ra pretreatment significantly reduced KD-induced myocardial inflammation and N-terminal pro B-type natriuretic peptide (NT-proBNP) release. Both MRI and echocardiographic studies on LCWE-injected KD mice demonstrated that IL-1Ra pretreatment results in an improved ejection fraction and a normalized left ventricular function. These findings further support the potential beneficial effects of IL-1Ra therapy in preventing the cardiovascular complications in acute KD patients, including the myocarditis and myocardial dysfunction associated with acute KD. Graphical Abstract: